(untitled) (Damascus University Journal for engineering sciences, 2023)
The study of evaluating the exposure to fields and electromagnetic waves on human is an important topic, especially with the presence of implants in various parts of the body, including the head, to reduce their negative effects. Therefore the aim of the research was to calculate and compare the specific absorption rate of bio tissues of the human head using the method of infinite difference in time domain FDTD (Finite Difference Time Domain) by CST (Computer Simulation Technology) program in two cases, the first one with the auditory brainstem implant in the ear and the second in the absence of the implant, the results showed a ​​increase 12.5% in the SAR(Specific Absorption Rate) in the presence of the implant at the frequency of 0.9GHz and 3% at The frequency of 1.8 GHz, and therefore this increase can lead to negative effects on the functioning of the auditory brainstem.